Health hazards related to Soba sewage treatment plant, Sudan - Rasha Osman Abdelwahab Abdelmoneim; Ranien Mohamed El Mortada Mahi Eldin Mahdi; Rawia Moawia Elamin Elahmer; Rogaya Adel Derar Elansary; Safaa Elsafi Widaa Mohamed; Said Hashim Ahmed Abdelgader; Sakina Salah Abbasher Ahmed; Sally Mohamed Alfatih Abdalrhman (AOSIS, 2017)
The aim of this study was to determine the health hazards acquired by the residents nearby Soba sewage treatment plant. A descriptive cross-sectional study was carried out in Soba locality, Khartoum, Sudan. An interviewer-administrated questionnaire was assigned to 462 residents of the area living in four geographically distributed squares around the sewage plant. The data was analyzed in SPSS; Cronbach's alpha reliability scale of measurement was used to check the internal validity of six variables related to the quality of life. A logistic regression analysis was used to assess the relationship between the health hazards and the quality of life. Among the 462 residents, difficulty in breathing (37.9%) and nausea (37.2) were the principal health hazards. Moreover, the residents had a satisfactory level of awareness (88.7%) about the health hazards. The utmost impact on the quality of life was psychological (97.2%). It was statistically correlated with the reported factors, which impacted the quality of life in the district as revealed by the Cronbach's alpha reliability test with absenteeism (P=0.026), disability (P=0.014), socialization (P=0.032) and death (P=0.016). A logistic regression analysis revealed chemical hazards had a statistically significant association (P<0.05) with quality of life of the residents of Soba district. The study strongly entails the fact that sewage treatment plants crave exceptional consideration from the concerned responsible authorities, together with the fact that the evolved health threats should be confronted with immense responsibility as soon as possible.